SEJARAH BERDIRINYA KABUPATEN BENGKALIS PROVINSI RIAU TAHUN 1958 (SUATU TINJAUAN HISTORIS) - Mauliddin, M.Rezeki; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The regency is the division of administrative territory in Indonesia after the province led by a regent. Districts and cities are autonomous regions which are authorized to regulate and manage their own government affairs. Bengkalis is one of the districts of Riau Province, Bengkalis is a large district in Riau Province. Established in 1958 in accordance with the establishment of a legitimate district government, many efforts were made by the government in establishing Bengkalis Regency. The purpose of this study is (a) To find out the origin of the name of Bengkalis Regency (b) To find out the past journey of Bengkalis Regency before its establishment as a district area (c) To find out the process of establishing Bengkalis Regency. The method of this research is qualitative descriptive. Qualitative method is a method that does not use numbers in data collection and in providing interpretation of the results. The results of this study are that Bengkalis Regency was established based on Law No.12 of 1956 State Gazette No. 25 of 1956 concerning the Establishment of District Autonomy in the Regional Environment of Central Sumatra Province, then after the establishment of Riau Province, Bengkalis officially stood as a legitimate district under the Act Emergency Act No. 19 of 1957, then invited back under Law No. 61 of 1958.Key Words: Establishment, Bengkalis Regency